2014
DOI: 10.1128/aac.02955-14
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Mechanistic Studies of Brilacidin, Daptomycin, and the Antimicrobial Peptide LL16

Abstract: b Brilacidin (PMX30063) has shown potent bactericidal activity against drug-resistant and -susceptible strains of multiple Gramnegative and Gram-positive pathogens. In this study, we demonstrate that brilacidin causes membrane depolarization in the Gram-positive bacterium Staphylococcus aureus, to an extent comparable to that caused by the lipopeptidic drug daptomycin. Transcriptional profiling of Staphylococcus aureus by deep sequencing shows that the global response to brilacidin treatment is well correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
158
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(166 citation statements)
references
References 62 publications
6
158
0
2
Order By: Relevance
“…LL37 is a human, cationic, cathelicidin antimicrobial peptide that is active through bacterial membrane destabilization (48). LL37 is not only a marker of immune response but also an endogenous analogue to DAP (49). Our data echo previous findings demonstrating the synergistic effects of ␤-lactam agents on LL37 activity in E. faecalis, E. faecium, and Staphylococcus aureus (24,25,50,51).…”
Section: Discussionsupporting
confidence: 80%
“…LL37 is a human, cationic, cathelicidin antimicrobial peptide that is active through bacterial membrane destabilization (48). LL37 is not only a marker of immune response but also an endogenous analogue to DAP (49). Our data echo previous findings demonstrating the synergistic effects of ␤-lactam agents on LL37 activity in E. faecalis, E. faecium, and Staphylococcus aureus (24,25,50,51).…”
Section: Discussionsupporting
confidence: 80%
“…The current findings are consistent with prior data which suggested that GraSR is involved in stress responses and potential mechanisms of action of other peptide anti-infective agents, including daptomycin, LL-37, and the experimental agent brilacidin (20). Other studies have suggested that GraX as well as distinct two-component regulatory systems, such as VraSR and NsaSR, are also involved in S. aureus responses to antibiotics (21,22).…”
Section: Fig 3 Quantitative Mechanisms Of Hdps Againstsupporting
confidence: 82%
“…Antimicrobial peptides (AMPs) have been proposed as candidates because of their novel mechanisms of action. AMPs are produced by diverse organisms, including microbes, plants, insects, and mammals, and may replace or complement traditional antibiotics in settings where antibiotics alone have lost efficacy (12)(13)(14). Most AMPs interact with bacterial membranes and cause membrane depolarization, electrolyte leakage, and ultimately cell death (15), but others have cytoplasmic targets (16).…”
mentioning
confidence: 99%